Block or No-Block? Regional Anesthesia and Return-to-Sport Outcomes in Quadriceps Tendon Autograft ACL Reconstruction - Borchard, Seth M.; VanTienderen, Richard J.; Pitcher, Nicholas J.; McCormick, Elle M.; Westermann, Robert W. (The Journal of Knee Surgery, 2025)
This research aimed to compare return-to-sport (RTS) muscle strength testing in athletes 6 months following a quadriceps tendon (QT) autograft anterior cruciate ligament (ACL) reconstruction performed with or without a nerve block. Retrospective analysis of RTS strength testing in competitive or recreational athletes who had a QT ACL reconstruction at a Midwest academic referral center. There were 182 participants ranging from 12 to 29 years of age with a mean age of 16.9 years old. Patients were stratified into two groups based on whether they received an intraoperative nerve (adductor canal) block. Relevant tests performed during RTS testing included isokinetic quadriceps and hamstring strength (ISOK) in addition to limb symmetry and self-reported psychological readiness. Most patients underwent multiple RTS tests; for this study, we used the data from their initial test typically performed in the 6-month postoperative timeframe. Forty-three patients had an intraoperative nerve block, while 139 did not have a block. There were no observed statistically significant differences in quadriceps or hamstring strength when comparing the median scores of the nerve block and no-block groups across the major quantitative categories of isokinetic muscle strength, limb symmetry, tuck jump errors, or psychological readiness to return to sport. There was evidence of a relationship between increased graft thickness and decreased isokinetic quadriceps strength at both 60 and 300 deg/s in addition to lower self-reported confidence in readiness to RTS. No significant differences in functional strength testing or psychological readiness at 6 months were seen in ACL reconstruction involving QT grafts based on block status. There was evidence of a relationship between increased QT autograft thickness and decreased functional outcomes at 6 months. This research strengthens the case for leveraging an adductor canal block in QT ACL reconstruction involving young athletes as an effective tool for pain management without compromising muscle strength or RTS readiness. The level of evidence is III.
Keywords: orthopedic surgery; sports medicine; ACL reconstruction; quadriceps autograft